Hak-Hak Pekerja Magang Dalam Hubungan Industrial - Zahrani, Tsabita; Asih, Tika Fudi; Maharani, Shinta Dewi; Permatasari, Sevia; Lugina, Putri (Journal of Industrial Relations Studies, 2025)
In Indonesia, the implementation of internships is governed by Law No. 13 of 2003 on Manpower. Article 1 of the law defines internships as part of a work training system that is carried out in an integrated manner, combining education or training at institutions with hands-on work experience. This process is conducted under the guidance and supervision of instructors or experienced workers during the production of goods and/or services within a company, with the aim of developing specific skills or expertise. Internship programs play a crucial role in workforce development by bridging the gap between theoretical knowledge and real-world application. For individuals, internships offer practical experience, allowing them to gain insight into workplace culture, internalize professional ethics, and enhance both technical and interpersonal skills. For companies, internships serve as a strategic investment—providing opportunities to identify potential future employees, support skill development, and boost productivity. Ultimately, internships benefit both parties by cultivating a more prepared and competitive workforce